Bimodal nano composite material and wide-pH-range ion chromatography separation material
By using dual-modal nanocomposite materials in ion chromatography, combining electrostatic and hydrophilic interactions, highly efficient separation of anions and cations over a wide pH range was achieved. This solves the problems of single separation mode and poor pH adaptability in traditional ion chromatography, and improves separation efficiency and sensitivity.
Patent Information
- Application Number
- CN202511145876.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-15
- Publication Date
- 2025-11-21
AI Technical Summary
Existing ion chromatography techniques suffer from limited separation modes, poor pH adaptability, insufficient separation efficiency and sensitivity, difficulty in flexibly switching separation modes over a wide pH range, high mass transfer resistance, and low theoretical plate number, making it difficult to achieve efficient separation of trace ions.
A dual-modal nanocomposite material is used. By loading a dual-modal nanocomposite stationary phase and pH-responsive functional groups on a nano-silica substrate, the separation of anions and cations is achieved through the synergistic effect of electrostatic and hydrophilic interactions. Mesoporous nanoparticles are used to improve mass transfer efficiency, and carboxylic acid groups and quaternary ammonium groups are modified on the surface of the stationary phase to switch the separation mode at different pH values.
It achieves efficient separation of anions and cations over a wide pH range, improving separation efficiency and sensitivity, simplifying the operation process, reducing mass transfer resistance, increasing specific surface area and loading rate, and adapting to the analysis of complex samples.
Smart Images

Figure CN120984241A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of liquid phase ion chromatography analysis technology, and relates to a dual-modal nanocomposite material and a wide pH range ion chromatography separation material. Background Technology
[0002] Liquid chromatography-ion chromatography (LC-IGC), a type of high-performance liquid chromatography (HPLC), can accurately measure the content of anions and cations in water samples. It boasts low detection limits and high accuracy, and is widely used in water quality analysis in scientific research, biology, and pharmaceuticals. Currently, ion chromatography analyzers utilize high-pressure resin separation columns for ion separation, which have the following technical limitations:
[0003] Limited separation modes and poor pH adaptability are drawbacks of traditional ion chromatography. Traditional ion chromatography typically relies on a single stationary phase (such as sulfonic acid cation exchange resins or quaternary ammonium salt anion exchange resins), meaning that the same column cannot simultaneously separate cations and anions. This necessitates changing to different columns or system configurations, significantly increasing operational complexity and cost. Furthermore, the limited pH response range of functional groups in the stationary phase (e.g., carboxylic acid groups are only applicable to acidic conditions) makes it difficult to flexibly switch separation modes over a wide pH range (e.g., 0.1-14), limiting its adaptability to complex samples.
[0004] Insufficient separation efficiency and sensitivity. Traditional chromatographic columns often use large-particle-size packing materials or non-porous structures, resulting in low specific surface area, high mass transfer resistance, and low theoretical plate number, making it difficult to achieve efficient separation of trace ions (ppb level). When relying on a single conductivity detector, weakly dissociated ions (such as silicates and organic acids) have weak response signals and are easily affected by matrix interference (such as high-concentration salts), requiring complex pretreatment. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a dual-modal nanocomposite material and a wide pH range ion chromatography separation material, which can solve the problems of single separation mode, poor pH adaptability, and insufficient separation efficiency and sensitivity.
[0006] To achieve the above objectives, this invention discloses a method for preparing a dual-modal nanocomposite stationary phase, comprising the following steps:
[0007] 1) Preparation of silanized silicon dioxide;
[0008] 2) In-situ polymerization of zwitterionic polymers using silanized silica;
[0009] 3) A dual-modal nanocomposite stationary phase was prepared using the zwitterionic polymer.
[0010] A further improvement of the preparation method of the dual-modal nanocomposite stationary phase described in this invention is that:
[0011] Furthermore, the specific operation of step 1) is as follows:
[0012] Mesoporous silica particles are immersed in an aminopropyltriethoxysilane solution, and amino groups are introduced through the reaction of silanol groups with a silane coupling agent to obtain silanized silica.
[0013] Furthermore, the specific operation of step 2) is as follows:
[0014] Acrylic acid and vinylimidazole were dissolved in ethanol, and ammonium persulfate initiator was added to obtain a monomer solution.
[0015] Silanized silica is dispersed in a monomer solution and then reacted under nitrogen protection to form a copolymer coating layer, thus obtaining an amphoteric polymer.
[0016] Furthermore, the molar ratio of acrylic acid to vinylimidazole is 1:1.
[0017] Furthermore, the specific operation of step 3) is as follows:
[0018] The epoxy quaternary ammonium salt is reacted with the amino or hydroxyl groups in the zwitterionic polymer to introduce quaternary ammonium groups, resulting in a composite material. After washing, the composite material is vacuum dried to obtain a bimodal nanocomposite stationary phase.
[0019] Furthermore, the epoxy quaternary ammonium salt is 3-chloro-2-hydroxypropyltrimethylammonium chloride.
[0020] Furthermore, the composite material is a composite material with a carboxylic acid / quaternary ammonium group molar ratio of 1:1.
[0021] Furthermore, ethanol was used to clean the composite material.
[0022] Furthermore, the mesoporous silica particles have a particle size of 3–10 μm.
[0023] This invention discloses a wide pH range ion chromatography separation material, comprising a nano-silica substrate and a bimodal nanocomposite stationary phase and pH-responsive functional groups supported on the nano-silica substrate.
[0024] The present invention has the following beneficial effects:
[0025] In practical operation, the bimodal nanocomposite material and wide pH range ion chromatography separation material described in this invention consist of a bimodal nanocomposite stationary phase and pH-responsive functional groups supported on a nano-silica substrate. Anion and cation separation is achieved through a synergistic effect of electrostatic and hydrophilic interactions. The stationary phase surface is modified with carboxylic acid groups (for protonated adsorption of cations at pH 2-6) and quaternary ammonium groups (for deprotonated adsorption of anions at pH 8-12). Different separation modes are activated by switching the pH of the mobile phase. Mesoporous nanoparticles (pore size 5-10 nm) are used to improve mass transfer efficiency, with a specific surface area >300 m². 2 / g, with a loading rate >90%, to solve the problems of single separation mode, poor pH adaptability, and insufficient separation efficiency and sensitivity. Attached Figure Description
[0026] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:
[0027] Figure 1 This is a flowchart of the method of the present invention. Detailed Implementation
[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] In the description of this invention, it should be understood that the terms "comprising" and "including" indicate the presence of the described features, integrals, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integrals, steps, operations, elements, components and / or collections thereof.
[0030] It should also be understood that the terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. As used in this specification and the appended claims, the singular forms “a,” “an,” and “the” are intended to include the plural forms unless the context clearly indicates otherwise.
[0031] It should also be further understood that the term "and / or" as used in this specification and the appended claims refers to any combination and all possible combinations of one or more of the associated listed items, and includes such combinations. For example, A and / or B can represent three cases: A alone, A and B simultaneously, and B alone. Additionally, the character " / " in this invention generally indicates that the preceding and following objects have an "or" relationship.
[0032] It should be understood that although terms such as first, second, third, etc., may be used in the embodiments of the present invention to describe the preset range, these preset ranges should not be limited to these terms. These terms are only used to distinguish the preset ranges from one another. For example, without departing from the scope of the embodiments of the present invention, the first preset range may also be referred to as the second preset range, and similarly, the second preset range may also be referred to as the first preset range.
[0033] Depending on the context, the word "if" as used here can be interpreted as "when," "when," "in response to determination," or "in response to detection." Similarly, depending on the context, the phrase "if determination" or "if detection (of the stated condition or event)" can be interpreted as "when determination," "in response to determination," "when detection (of the stated condition or event)," or "in response to detection (of the stated condition or event)."
[0034] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0035] The accompanying drawings illustrate various structural schematic diagrams according to embodiments disclosed in this invention. These drawings are not to scale, and some details have been enlarged for clarity, and some details may have been omitted. The shapes of the various regions and layers shown in the drawings, as well as their relative sizes and positional relationships, are merely exemplary and may deviate from reality due to manufacturing tolerances or technical limitations. Furthermore, those skilled in the art can design regions / layers with different shapes, sizes, and relative positions as needed.
[0036] The preparation method of the dual-modal nanocomposite stationary phase of the present invention includes the following steps:
[0037] 1) Preparation of silanized silicon dioxide;
[0038] 11) Silanization treatment:
[0039] Mesoporous silica particles with a particle size of 3–10 μm are immersed in an aminopropyltriethoxysilane (APTES) solution. Amino groups (-NH2) are introduced through the reaction of silanol groups with silane coupling agents, thereby enhancing the loading capacity of subsequent polymers.
[0040] 12) Cleaning and drying:
[0041] Unreacted silane reagent was removed by washing with ethanol, and the product was dried under vacuum at 60°C for 12 h to obtain silanized silica.
[0042] 2) In-situ polymerization of zwitterionic polymers
[0043] Monomer blending:
[0044] Acrylic acid (from the carboxylic acid group) and vinylimidazole (from the cationic group) were dissolved in ethanol at a molar ratio of 1:1, and ammonium persulfate initiator was added to obtain a monomer solution.
[0045] Graft polymerization: Silanized silica is dispersed in a monomer solution and then reacted at 60°C under nitrogen protection for 12 hours to form a poly(vinylimidazolium-co-acrylic acid) copolymer coating layer. The polymer chains can then be uniformly grafted through free radical polymerization to obtain a zwitterionic polymer.
[0046] 3) pH-responsive functional group modification
[0047] Quaternization reaction:
[0048] An epoxy quaternary ammonium salt (such as 3-chloro-2-hydroxypropyltrimethylammonium chloride) is reacted with an amino or hydroxyl group in a zwitterionic polymer to introduce a quaternary ammonium group. The reaction conditions are 60°C and 8 h, resulting in a composite material with a carboxylic acid / quaternary ammonium group molar ratio of 1:1.
[0049] Post-processing: Unreacted quaternary ammonium salts were removed by centrifugation with ethanol, and then the mixture was vacuum dried at 60°C for 24 hours to obtain a bimodal nanocomposite stationary phase.
[0050] Example 1
[0051] The preparation method of the dual-modal nanocomposite stationary phase of the present invention includes the following steps:
[0052] 1) Preparation of silanized silicon dioxide;
[0053] 11) Silanization treatment:
[0054] Mesoporous silica particles with a particle size of 3 μm were immersed in an aminopropyltriethoxysilane (APTES) solution. Amino groups (-NH2) were introduced through the reaction of silanol groups with silane coupling agents, thereby enhancing the loading capacity of subsequent polymers.
[0055] 12) Cleaning and drying:
[0056] Unreacted silane reagent was removed by washing with ethanol, and the product was dried under vacuum at 60°C for 12 h to obtain silanized silica.
[0057] 2) In-situ polymerization of zwitterionic polymers
[0058] Monomer blending:
[0059] Acrylic acid (from the carboxylic acid group) and vinylimidazole (from the cationic group) were dissolved in ethanol at a molar ratio of 1:1, and ammonium persulfate initiator was added to obtain a monomer solution.
[0060] Graft polymerization: Silanized silica is dispersed in a monomer solution and then reacted at 60°C under nitrogen protection for 12 hours to form a poly(vinylimidazolium-co-acrylic acid) copolymer coating layer. The polymer chains can then be uniformly grafted through free radical polymerization to obtain a zwitterionic polymer.
[0061] 3) pH-responsive functional group modification
[0062] Quaternization reaction:
[0063] 3-Chloro-2-hydroxypropyltrimethylammonium chloride was reacted with an amino or hydroxyl group in a zwitterionic polymer to introduce a quaternary ammonium group. The reaction conditions were 60°C and 8 h, resulting in a composite material with a carboxylic acid / quaternary ammonium group molar ratio of 1:1.
[0064] Post-processing: Unreacted quaternary ammonium salts were removed by centrifugation with ethanol, and then the mixture was vacuum dried at 60°C for 24 hours to obtain a bimodal nanocomposite stationary phase.
[0065] Example 2
[0066] The preparation method of the dual-modal nanocomposite stationary phase of the present invention includes the following steps:
[0067] 1) Preparation of silanized silicon dioxide;
[0068] 11) Silanization treatment:
[0069] Mesoporous silica particles with a particle size of 5 μm were immersed in an aminopropyltriethoxysilane (APTES) solution. Amino groups (-NH2) were introduced through the reaction of silanol groups with silane coupling agents, thereby enhancing the loading capacity of subsequent polymers.
[0070] 12) Cleaning and drying:
[0071] Unreacted silane reagent was removed by washing with ethanol, and the product was dried under vacuum at 60°C for 12 h to obtain silanized silica.
[0072] 2) In-situ polymerization of zwitterionic polymers
[0073] Monomer blending:
[0074] Acrylic acid (from the carboxylic acid group) and vinylimidazole (from the cationic group) were dissolved in ethanol at a molar ratio of 1:1, and ammonium persulfate initiator was added to obtain a monomer solution.
[0075] Graft polymerization: Silanized silica is dispersed in a monomer solution and then reacted at 60°C under nitrogen protection for 12 hours to form a poly(vinylimidazolium-co-acrylic acid) copolymer coating layer. The polymer chains can then be uniformly grafted through free radical polymerization to obtain a zwitterionic polymer.
[0076] 3) pH-responsive functional group modification
[0077] Quaternization reaction:
[0078] 3-Chloro-2-hydroxypropyltrimethylammonium chloride was reacted with an amino or hydroxyl group in a zwitterionic polymer to introduce a quaternary ammonium group. The reaction conditions were 60°C and 8 h, resulting in a composite material with a carboxylic acid / quaternary ammonium group molar ratio of 1:1.
[0079] Post-processing: Unreacted quaternary ammonium salts were removed by centrifugation with ethanol, and then the mixture was vacuum dried at 60°C for 24 hours to obtain a bimodal nanocomposite stationary phase.
[0080] Example 3
[0081] The preparation method of the dual-modal nanocomposite stationary phase of the present invention includes the following steps:
[0082] 1) Preparation of silanized silicon dioxide;
[0083] 11) Silanization treatment:
[0084] Mesoporous silica particles with a particle size of 10 μm were immersed in an aminopropyltriethoxysilane (APTES) solution. Amino groups (-NH2) were introduced through the reaction of silanol groups with silane coupling agents, thereby enhancing the loading capacity of subsequent polymers.
[0085] 12) Cleaning and drying:
[0086] Unreacted silane reagent was removed by washing with ethanol, and the product was dried under vacuum at 60°C for 12 h to obtain silanized silica.
[0087] 2) In-situ polymerization of zwitterionic polymers
[0088] Monomer blending:
[0089] Acrylic acid (from the carboxylic acid group) and vinylimidazole (from the cationic group) were dissolved in ethanol at a molar ratio of 1:1, and ammonium persulfate initiator was added to obtain a monomer solution.
[0090] Graft polymerization: Silanized silica is dispersed in a monomer solution and then reacted at 60°C under nitrogen protection for 12 hours to form a poly(vinylimidazolium-co-acrylic acid) copolymer coating layer. The polymer chains can then be uniformly grafted through free radical polymerization to obtain a zwitterionic polymer.
[0091] 3) pH-responsive functional group modification
[0092] Quaternization reaction:
[0093] 3-Chloro-2-hydroxypropyltrimethylammonium chloride was reacted with an amino or hydroxyl group in a zwitterionic polymer to introduce a quaternary ammonium group. The reaction conditions were 60°C and 8 h, resulting in a composite material with a carboxylic acid / quaternary ammonium group molar ratio of 1:1.
[0094] Post-processing: Unreacted quaternary ammonium salts were removed by centrifugation with ethanol, and then the mixture was vacuum dried at 60°C for 24 hours to obtain a bimodal nanocomposite stationary phase.
[0095] Example 4
[0096] The preparation method of the dual-modal nanocomposite stationary phase of the present invention includes the following steps:
[0097] 1) Preparation of silanized silicon dioxide;
[0098] 11) Silanization treatment:
[0099] Mesoporous silica particles with a particle size of 8 μm were immersed in an aminopropyltriethoxysilane (APTES) solution. Amino groups (-NH2) were introduced through the reaction of silanol groups with silane coupling agents, thereby enhancing the loading capacity of subsequent polymers.
[0100] 12) Cleaning and drying:
[0101] Unreacted silane reagent was removed by washing with ethanol, and the product was dried under vacuum at 60°C for 12 h to obtain silanized silica.
[0102] 2) In-situ polymerization of zwitterionic polymers
[0103] Monomer blending:
[0104] Acrylic acid (from the carboxylic acid group) and vinylimidazole (from the cationic group) were dissolved in ethanol at a molar ratio of 1:1, and ammonium persulfate initiator was added to obtain a monomer solution.
[0105] Graft polymerization: Silanized silica is dispersed in a monomer solution and then reacted at 60°C under nitrogen protection for 12 hours to form a poly(vinylimidazolium-co-acrylic acid) copolymer coating layer. The polymer chains can then be uniformly grafted through free radical polymerization to obtain a zwitterionic polymer.
[0106] 3) pH-responsive functional group modification
[0107] Quaternization reaction:
[0108] 3-Chloro-2-hydroxypropyltrimethylammonium chloride was reacted with an amino or hydroxyl group in a zwitterionic polymer to introduce a quaternary ammonium group. The reaction conditions were 60°C and 8 h, resulting in a composite material with a carboxylic acid / quaternary ammonium group molar ratio of 1:1.
[0109] Post-processing: Unreacted quaternary ammonium salts were removed by centrifugation with ethanol, and then the mixture was vacuum dried at 60°C for 24 hours to obtain a bimodal nanocomposite stationary phase.
[0110] Finally, specific experimental methods can be used to verify the performance indicators of the above-mentioned stationary phase, such as pore size, specific surface area, surface charge, and chromatographic separation performance, as follows:
[0111] Pore size and specific surface area: The mesoporous structure was verified by nitrogen adsorption-desorption (BET) method, with a pore size distribution of 5-10 nm and a specific surface area >300 m². 2 / g.
[0112] Surface charge test: The surface potential at different pH values was measured using a Zeta potentiometer to confirm the pH response characteristics of carboxylic acid and quaternary ammonium groups. The potential was +25mV at pH 3 and -30mV at pH 10.
[0113] Chromatographic performance testing: After packing a PEEK column, the cation (Li+ / Na+) ratio was verified using mobile phases of methanesulfonic acid (pH 3.0) and borate (pH 10.5), respectively. + / K + The separation degree between the ions and anions (F- / Cl- / SO42-) is higher than 1.5.
[0114] The wide pH range ion chromatography separation material of this invention comprises a nano-silica substrate, a bimodal nanocomposite stationary phase supported on the nano-silica substrate, and pH-responsive functional groups. Anion and cation separation is achieved through the synergistic effect of electrostatic and hydrophilic interactions. The stationary phase surface is modified with carboxylic acid groups (protonated adsorption of cations at pH 2-6) and quaternary ammonium groups (deprotonated adsorption of anions at pH 8-12). Different separation modes are activated by switching the pH of the mobile phase. Mesoporous nanoparticles (pore size 5-10 nm) are used to improve mass transfer efficiency, with a specific surface area >300 m². 2 / g, loading rate >90%.
[0115] It should be noted that the present invention has the following characteristics:
[0116] The core of the dual-modal nanocomposite stationary phase design lies in combining the electrostatic interactions of zwitterionic polymers with the dynamic charge regulation capabilities of pH-responsive functional groups to achieve efficient separation of anions and cations over a wide pH range (pH 2-12) through synergistic effects. The specific design route is as follows:
[0117] 1) Synergistic effect of hydrophilicity and electrostatics of zwitterionic polymers.
[0118] 2) Zwitterionic polymers, such as thiobetaine and poly(vinylimidazolium-co-acrylic acid), possess both positive and negative charged groups, forming a hydrophilic interfacial layer. In chromatographic separation, hydrophilic interactions dominate the retention of polar compounds, while electrostatic interactions regulate ion selectivity through charge attraction or repulsion. Thiobetaine zwitterionic stationary phases can enhance the retention of polar compounds through hydrogen bonding and dipole interactions.
[0119] 3) Dynamic charge regulation of pH-responsive functional groups.
[0120] The carboxylic acid group protonates under acidic conditions (pH 2-6) (-COOH → -COO-), becoming negatively charged and adsorbing cations (such as Li+, Na+) through electrostatic interactions. + ); while the quaternary ammonium group is deprotonated (-N) under alkaline conditions (pH 8-12). + R3→-N + R3), with a positively charged surface, adsorbs anions (such as F- and Cl-). By dynamically switching the pH of the mobile phase, the surface charge of the stationary phase reverses, activating different separation modes and achieving dual-mode separation of anions and cations in a single column.
[0121] 4) Enhanced mass transfer due to nanoporous structure.
[0122] Utilizing mesoporous silica substrates (pore size 5-10 nm, specific surface area > 300 m²) 2 The high specific surface area and ordered pore structure significantly improve mass transfer efficiency. The high specific surface area and ordered pore structure shorten the ion diffusion path and reduce mass transfer resistance, thereby increasing the separation rate and the number of theoretical plates (theoretical plate number > 20,000 / m).
[0123] Other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and disclosure of the invention. This application is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein. The specification and examples are to be considered exemplary only, and the true scope and spirit of the invention are indicated by the following claims.
[0124] It should be understood that the present invention is not limited to the precise structure described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.
[0125] The above description is merely a preferred embodiment of the present invention and does not constitute any limitation on the present invention. Any simple modifications, alterations, or equivalent structural changes made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A method for preparing a dual-modal nanocomposite stationary phase, characterized in that, Includes the following steps: 1) Preparation of silanized silicon dioxide; 2) In-situ polymerization of zwitterionic polymers using silanized silica; 3) A dual-modal nanocomposite stationary phase was prepared using the zwitterionic polymer.
2. The method for preparing a dual-modal nanocomposite stationary phase according to claim 1, characterized in that, The specific operation of step 1) is as follows: Mesoporous silica particles are immersed in an aminopropyltriethoxysilane solution, and amino groups are introduced through the reaction of silanol groups with a silane coupling agent to obtain silanized silica.
3. The method for preparing a dual-modal nanocomposite stationary phase according to claim 1, characterized in that, The specific operation of step 2) is as follows: Acrylic acid and vinylimidazole were dissolved in ethanol, and ammonium persulfate initiator was added to obtain a monomer solution. Silanized silica is dispersed in a monomer solution and then reacted under nitrogen protection to form a copolymer coating layer, thus obtaining an amphoteric polymer.
4. The method for preparing a dual-modal nanocomposite stationary phase according to claim 3, characterized in that, The molar ratio of acrylic acid to vinylimidazole is 1:
1.
5. The method for preparing a dual-modal nanocomposite stationary phase according to claim 1, characterized in that, The specific operation of step 3) is as follows: The epoxy quaternary ammonium salt is reacted with the amino or hydroxyl groups in the zwitterionic polymer to introduce quaternary ammonium groups, resulting in a composite material. After washing, the composite material is vacuum dried to obtain a bimodal nanocomposite stationary phase.
6. The method for preparing a dual-modal nanocomposite stationary phase according to claim 5, characterized in that, The epoxy quaternary ammonium salt is 3-chloro-2-hydroxypropyltrimethylammonium chloride.
7. The method for preparing a dual-modal nanocomposite stationary phase according to claim 5, characterized in that, The composite material is a composite material with a carboxylic acid / quaternary ammonium group molar ratio of 1:
1.
8. The method for preparing a dual-modal nanocomposite stationary phase according to claim 5, characterized in that, Ethanol was used to clean the composite material.
9. The method for preparing a dual-modal nanocomposite stationary phase according to claim 2, characterized in that, The mesoporous silica particles have a particle size of 3–10 μm.
10. A wide pH range ion chromatography separation material, characterized in that, The invention includes a nano-silica substrate and a bimodal nanocomposite stationary phase and pH-responsive functional groups prepared by any one of claims 1-9 on a nano-silica substrate.